VIBRATION ANALYSIS OF FLUID-STRUCTURE INTERACTION USING TUNED MASS DAMPERS - Javanshir, Ilgar; Zarepour, Gholamreza (Journal of Applied Engineering Science, 2020)
This paper has investigated the semi-analytical analysis of the solid-fluid interaction vibration in the presence of concentrated mass-spring-damper vibration absorber. The nonlinear partial differential equations of motion are derived by considering von Karman-type large deformations and viscoelastic behaviour. Fluid-structure interaction is modelled by using an acceleration coupling model in which a nonlinear Van der Pol oscillator simulates fluctuating nature of the vortex street. The nonlinear equations are discretized via the Galerkin approach, and the obtained equations are numerically solved by applying the Runge–Kutta method. Eventually, the dynamic response, phase plane plots, and variations of maximum amplitude in terms of fluid velocity for different parameters are extracted. The results reveal that utilizing vibration absorber leads to a signifi cant effect on the dynamic characteristics of the system, displaces the lock-in phenomenon, and remarkably reduce the amplitude of the system oscillations.